Antibacterial activity of coriander seeds extract (Coriandrum sativum) against the growth of Streptococcus mutans - Kodariah, Liah; Amaliah, Eka Yuliani; Fadhillah, Tyas Ismi (Journal of Indonesian Medical Laboratory and Science, 2024)
Background: Streptococcus mutans is the main cause of dental caries, previously known as part of the normal flora in the oral cavity which plays a role in the process of fermenting carbohydrates to produce acid, and causes tooth demineralization. Chemical-based medicinal products such as toothpaste and mouthwash. Continuous use of chemicals can cause side effects for users such as hypersensitivity, therefore an alternative treatment from natural ingredients such as coriander seeds which can inhibit bacterial growth is needed. Objective: This research aims to determine the lowest concentration of coriander seed extract in 0,75%, 1.5%, 3% inhibiting the growth of Streptococcus mutans. Methods: This study was conducted by soaking the test discs in coriander seed extract concentrations of 0.75%, 1.5% and 3%. each disc was inserted into the bacterial culture to be cultured, incubated and seen whether there was a clear zone or not. Result: Test results showed a clear zone at a concentration 1.5% with an average diameter of 1.5 mm, at concentration of 3% an average diameter of 3.7 mm and at concentration of 0.75% did not show clear zone. Conclusion: Based on the results of the study, the lowest concentration of coriander seed extract was obtained which was able to inhibit the growth of Streptococcus mutans bacteria, is at concentration of 1.5%, the diameter of the inhibition zone of coriander seed extract had weak antibacterial activity.